Assessment of Waianae’s Vulnerability to a Category 4 Hurricane - Jafar, Jafar; Jain, Shubhanshu; Erlangga, Wisnu (Sumatra Journal of Disaster, Geography and Geography Education, 2024)
This research assesses the vulnerability of Waianae, a Census County Division on the northwest quadrant of Oahu, to a Category 4 hurricane. Combining socio-economic and risk assessment analyses, the study reveals that Waianae is highly susceptible to hurricane impacts, given its historical exposure and socio-economic disparities. The socio-economic vulnerabilities, including lower income, higher poverty rates, and increased unemployment, are compounded by physical vulnerabilities, such as limited access via Farrington Highway. Utilizing tools like HAZUS-MH and ArcGIS, the study quantifies potential damages, debris generation, social impacts, and economic losses in the event of a hurricane. The findings emphasize the urgent need for resilience-building measures, including local job creation, development of emergency shelters, and exploration of alternative evacuation routes. Addressing these vulnerabilities will enhance Waianae's preparedness and mitigate the potential impact of future hurricanes, fostering a more resilient and secure community.